2020
DOI: 10.1192/bjo.2020.41
|View full text |Cite
|
Sign up to set email alerts
|

Experience of transfer from child to adult mental health services of young people with autism spectrum disorder

Abstract: Background Transition from child-centred to adult mental health services has been reported as challenging for young people. It can be especially difficult for young people with autism spectrum disorder (ASD) as they manage the challenges of adolescence and navigate leaving child and adolescent mental health services (CAMHS). Aims This study examines the predictors of transfer to adult mental health services, and using a qualitative analysis, explores the young people’s experiences of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…3-5 8 10 11 Only few prospective studies have been conducted, mostly in small samples, within one CAMHS or within subsamples such as young people with autism spectrum disorders (ASD). 6 7 12 Only 1 study, 12 investigating 118 young people with ASD, included self-reported and parent-reported information. To date, no studies have been conducted that compare longitudinal mental health outcomes of young people who transition to AMHS with those who do not.…”
Section: Introductionmentioning
confidence: 99%
“…3-5 8 10 11 Only few prospective studies have been conducted, mostly in small samples, within one CAMHS or within subsamples such as young people with autism spectrum disorders (ASD). 6 7 12 Only 1 study, 12 investigating 118 young people with ASD, included self-reported and parent-reported information. To date, no studies have been conducted that compare longitudinal mental health outcomes of young people who transition to AMHS with those who do not.…”
Section: Introductionmentioning
confidence: 99%
“…Data extraction – Neurodevelopmental disorders). Three studies included young people with ASD (Laxman, Taylor, DaWalt, Greenberg, & Mailick, 2019; Merrick et al., 2020; Tunesi, Bosio, & Russo, 2019), four included young people with any neurodevelopmental condition (Asl, 2014; Maslow, 2016; Patwardhan, Singh, & Kanster, 2019; Singh et al., 2021), one focused on learning disabilities (Sharif, 2021), one on hyperkinetic disorder (Blasco‐Fontecilla et al., 2012) and the remainder focussed on ADHD (Ayyash et al., 2018; Eke et al., 2019; Eke et al., 2018; Heron et al., 2020; Janssens et al., 2020; Magon, Latheesh, & Muller, 2015; McCarthy et al., 2009; McNicholas & Singh, 2015; Moosa & Sandhu, 2015; Ogundele, 2013; Ogundele & Omenaka, 2012; Price, Newlove‐Delgado, et al., 2019; Reale et al., 2018; Reale, Frassica, Gollner, & Bonati, 2015; Tatlow‐Golden et al., 2018). However, most studies included young people with comorbidity, including those with comorbid ADHD/ASD.…”
Section: Transition For Those With Neurodevelopmental Disordersmentioning
confidence: 99%
“…This variation in the proportion referred may relate to different health systems, changes over time and inclusion criteria. Predictors of referral and acceptance into adult services identified included female gender, comorbidity and pharmacological or combined treatment of ADHD (Merrick et al., 2020).…”
Section: Transition For Those With Neurodevelopmental Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer from child to adult care is called transition, which includes a series of steps to follow and whose main objective is to ensure the continuity of care (Schor, 2015). Over the last two decades, the importance of transition care has been increasingly recognized within both paediatric and adult sectors, also for other chronic disorders (Davignon et al, 2018; Elias & White, 2018; Levy et al, 2020; Merrick et al, 2020; Paton & Hiscock, 2019; Sezgin et al, 2020). In Europe, many projects (Janssens et al, 2020; Lepiece et al, 2020; Paul et al, 2013; Singh et al, 2008, 2010, 2017), programmes and register networks (Bonati et al, 2018; Jonsson et al, 2021; Poulton, 2017) concerning transition were created; also in Italy, a scoping review was conducted (Reale & Bonati, 2015); all these actions have highlighted the needing of a standard transition protocol with shared guidelines, formal policies and more investments in healthcare service delivery.…”
Section: Introductionmentioning
confidence: 99%